2023
DOI: 10.1002/advs.202202964
|View full text |Cite
|
Sign up to set email alerts
|

M2 Macrophage‐Derived sEV Regulate Pro‐Inflammatory CCR2+ Macrophage Subpopulations to Favor Post‐AMI Cardiac Repair

Abstract: Tissue‐resident cardiac macrophage subsets mediate cardiac tissue inflammation and repair after acute myocardial infarction (AMI). CC chemokine receptor 2 (CCR2)‐expressing macrophages have phenotypical similarities to M1‐polarized macrophages, are pro‐inflammatory, and recruit CCR2+ circulating monocytes to infarcted myocardium. Small extracellular vesicles (sEV) from CCR2̶ macrophages, which phenotypically resemble M2‐polarized macrophages, promote anti‐inflammatory activity and cardiac repair. Here, the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…Concerning this, it has been reported that macrophage polarization to an M2 profile is associated with rescued function and improved heart repair in acute myocardial infarction. 79 In summary, here we show for the first time that in the early stages of experimental Chagas disease, fenofibrate significantly increased the proportion of cardiac MdMΦ and MΦ with a marked restorative profile. These findings were accompanied by switch toward to a noninflammatory microenvironment which correlates with reduced fibrosis and attenuates ventricular function.…”
Section: ■ Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Concerning this, it has been reported that macrophage polarization to an M2 profile is associated with rescued function and improved heart repair in acute myocardial infarction. 79 In summary, here we show for the first time that in the early stages of experimental Chagas disease, fenofibrate significantly increased the proportion of cardiac MdMΦ and MΦ with a marked restorative profile. These findings were accompanied by switch toward to a noninflammatory microenvironment which correlates with reduced fibrosis and attenuates ventricular function.…”
Section: ■ Discussionsupporting
confidence: 54%
“…This correlates with the restored cardiac function. Concerning this, it has been reported that macrophage polarization to an M2 profile is associated with rescued function and improved heart repair in acute myocardial infarction …”
Section: Discussionmentioning
confidence: 99%
“…CCR2-positive (CCR2+) inflammatory monocytes are crucial early response immune cells, and excessive infiltration or accumulation vitiates the remission of inflammation and promotes disease progression [ 15 , 16 ]. CCR2+ monocytes appear pro-inflammatory activity and differentiate into monocyte-derived CCR2+ macrophages with features similar to classically activated macrophages (M1-like macrophages), whereas CCR2-negative (CCR2-) macrophages have phenotypic characteristics similar to alternately activated macrophages (M2-like macrophages) [ 17 ]. CCR2+ monocytes are recruited into the glomerular capillaries and may be precursors of immature macrophages in the nephritic kidney [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are naturally occurring nanosized membrane vesicles encased by phospholipid bilayers ranging in size from 30 to 150 nm. [12] As a unique class of natural nanomaterials, exosomes can act as mediators of genetic information, carry and deliver biological signals to neighboring and distant cells, regulate the physiological and pathological state of recipient cells, and participate in the progression of various diseases. [13] The endogenous and heterogeneous nature of exosomes gives them a broad and unique advantage over synthetic carriers such as liposomes and nanoparticles in the diagnosis and treatment of periodontitis.…”
Section: Introductionmentioning
confidence: 99%